Roveteer: An Innovative Digital Solution for Mangrove Forest Conservation Volunteer Management in Kota Pari Village - Darmeli Nasution; Indri Sulistianingsih; Ahmad Akbar; Bagus Setiawan (Journal of Information Technology, computer science and Electrical Engineering, 2024)
Mangrove forest conservation requires effective volunteer management and technological support. This study developed the Roveteer application, a specialized digital platform designed to optimize volunteer coordination and engagement in mangrove conservation efforts at Kota Pari Village. The research employed a user-centered design approach, integrating technological innovation with local ecological conservation needs. Through systematic analysis of volunteer management challenges, the application was developed to streamline recruitment, task allocation, tracking, and impact assessment of conservation activities. The Roveteer platform features include real-time volunteer registration, activity scheduling, performance monitoring, and geographical mapping of conservation zones. Prototype testing demonstrated the application's potential to enhance volunteer participation, improve communication efficiency, and provide data-driven insights into conservation efforts. Results indicated a 35% improvement in volunteer coordination and a 40% increase in documented conservation activities compared to traditional management methods. The Roveteer application represents a significant technological innovation in local environmental preservation, offering a replicable model for community-driven conservation technology that can be adapted to similar ecological contexts.